(untitled) (Research, Society and Development, 2020)
Adequate management of diabetes requires professional improvement programs. This study aimed to analyze the effect of a simulation activity on the acquisition of knowledge about blood glucose monitoring and hypoglycemia management. The study employed a pre-post intervention approach and was carried out in a university hospital located in Brazil. The participants were 82 graduating nursing students and nursing professionals studying/working at the university hospital. The intervention consisted of theoretical sessions, a practical simulation about glycemic monitoring and hypoglycemia management, and the pre- and post-tests. The simulation consisted of a rubber hand mannequin that allows simulating the glucose testing. There was a significant increase in knowledge after intervention with the total number of correct answers increasing from 186 in the pre-test to 326 in the post-test (+140, p < .001). The intervention was effective in increasing the participants’ knowledge about glycemic monitoring and hypoglycemia management, favoring a better nursing care for people with diabetes.